Strategic Bank Liability Structure Under Capital Requirements - Sundaresan, Suresh; Wang, Zhenyu (Management Science, 2023)
Banks strategically choose and dynamically restructure deposits and nondeposit debt in response to the minimum requirements on total capital and tangible equity. We derive the optimal strategic liability structure and show that it minimizes the protection for deposits conditional on capital requirements. Although, given any liability structure, regulators can set capital requirements high enough to remove the incentive for risk substitution, the strategic response to the capital requirements always preserves this incentive. Banks reduce leverage but increase the proportion of nondeposit debt if regulations raise the capital requirements. This paper was accepted by Lukas Schmid, finance. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2022.4570 .